PALEOENVIRONMENTAL RECONSTRUCTION FROM BENTHIC FORAMINIFERAL ASSEMBLAGES OF EARLY HOLOCENE, SHALLOW MARINE DEPOSITS IN GOMBONG, CENTRAL JAVA - Luli Gustiantini; Kresna Tri Dewi; Anne Muller; Praptisih Praptisih (BULLETIN OF THE MARINE GEOLOGY, 2007)
A 30m-long sediment core covering the Holocene period was taken from the area of Gombong in the southern part of Central Java. The sediments were deposited in a shallow marine to lagoonal environment that was confirmed by the dominance of Ammonia beccarii along the core intervals. In addition, the species Quinqueloculina poeyana, Miliolinella lakemacquariensis, and Miliolinella subrotunda were also found in the sediments that are typical of normal shallow marine conditions. The decrease and increase in the abundance of these species throughout the core is an expression of sea level change in the area, which results the environmental changes. Low sea level is expressed by the dominance of Ammonia beccarii, and the low abundances or absence of the other three species. In contrast, high sea level stands are reflected by the presence of all four species. The high sea level would imply favorable conditions for benthic foraminifera because it would result in normal shallow marine conditions in the area. Finally, from this benthic assemblages study, it can be assumed that the environmental transformation from the originally shallow marine environment into land was occurred at level 5.5m depths of the sediment core, when all benthic foraminifera were terminated, including Ammonia beccarii. These new results from the shallow marine deposits in the Gombong area are a new contribution to the understanding of paleoenvironmental change in the region, which in turn is important for understanding sea level change as well as climate change in the region. Keywords: Benthic foraminifera, Holocene, paleoenvironmental changes, sea level changes Southcoast of Central Java Sebuah percontoh sedimen bor sepanjang 30m yang berumur Holosen diambil dari daerah Gombong, bagian selatan Jawa Tengah. Percontoh sedimen diendapkan pada lingkungan laut dangkal –laguna, berdasarkan kelimpahan foraminifera bentik Ammonia beccarii di sepanjang sedimen bor. Selain itu ditemukan juga spesies-spesies Quinqueloculina poeyana, Miliolinella lakemacquariensis, dan Miliolinella subrotunda, yang merupakan penciri lingkungan laut dangkal dengan kondisi normal. Penurunan dan kenaikan dari kelimpahan masing-masing spesies foraminifera bentik di atas, dapat mencerminkan perubahan permukaan air laut daerah studi, yang menghasilkan terjadinya perubahan lingkungan. Penurunan muka air laut dapat dicirikan dengan hadirnya Ammonia beccarii yang sangat dominan, sementara spesies lainnya cenderung berkurang bahkan hampir tidak ada. Sebaliknya ketika muka air laut naik, maka keempat spesies foraminifera tersebut cenderung hadir dengan jumlah yang seimbang satu sama lainnya. Kenaikan muka air laut akan menghasilkan lingkungan laut normal yang merupakan kondisi ideal bagi foraminifera. Akhirnya, dari kajian perubahan kelimpahan foraminifera bentik ini, dapat diperkirakan bahwa pada level kedalaman bor 5,5m, terjadi perubahan lingkungan dari lingkungan laut dangkal-laguna menjadi daratan, yang ditandai dengan musnahnya semua jenis foraminifera bentik, termasuk Ammonia beccarii. HAsil kajian ini merupakan kontribusi baru untuk mempelajari perubahan lingkungan pada lokasi penelitian, terutama penting untuk lebih mengerti mengenai perubahan muka air laut dan perubahan iklim. Keywords: Benthic foraminifera, Holocene, paleoenvironmental changes, sea level changes